The correlation between conventional echocardiography and two‐dimensional speckle strain imaging for evaluating left atrial function in patients with moderate to severe mitral stenosis. Issue 10 (3rd July 2018) - Sahebjam, Mohammad; Montazeri, Vahide; Zoroufian, Arezoo; Hosseinsabet, Ali; Lotfi‐Tokaldany, Masoumeh; Jalali, Arash
Abstract : Aim: We intended to assess the left atrial deformation parameters, using two‐dimensional speckle tracking (2DSTE) and transesophageal echocardiography (TEE), and determine the correlation between these two techniques in order to recognize the patients at risk for cardioembolic events. Method: Strain and strain rate were measured using 2DSTE among 26 patients in sinus rhythm, with isolated moderate to severe mitral stenosis. Left atrial (LA) volume parameters (maximum, minimum and preatrial contraction) were measured. Among 26 patients, TEE was performed to detect left atrial thrombosis or spontaneous echo contrast. Left atrial appendage velocity (LAAV) was also assessed. Results: A significant correlation was observed between LAAV and the average value of left atrial peak systolic strain (LA‐RES) ( r  = 0.638, P  = 0.001). The sensitivity and specificity of mean LA‐RES (cutoff = 16.75%) for detecting LAAV < 25 cm/s were 88.9% and 80%, respectively. The sensitivity and specificity of mean LA‐RES (cutoff = 18.14%) for detecting LAAV < 25 cm/s and/or dense smoky pattern were 77.8% and 83.3%, respectively, and those of left atrial maximum volume indexed for body surface area(cutoff = 50.75 cc/m 2 ), for discriminating LAAV < 25 cm/s and/or dense smoky pattern, were 73.3% and 83.3%, respectively. A meaningful correlation was witnessed between mean LA‐RES and left atrial ejection fraction ( r  = 0.736, P  < 0.001), and left atrial expansion index ( r  = 0.743, P  < 0.001). Conclusion: The average value of left atrial reservoir function using 2DSTE can be used as a predictive factor for detecting LAAV < 25 cm/s and/or dense SEC and thus recognizing high‐risk patients for cardioembolic events with moderate to severe mitral stenosis. In addition, assessment of LA function and LA volume can also be helpful.